The History of the Linear No-Threshold Model and Recommendations for a Path Forward. Issue 2 (February 2023) - Cardarelli, John; Hamrick, Barbara; Sowers, Dan; Burk, Brett
Abstract: The intent of this paper and the accompanying video series is to inform the scientific community about the historical foundations that underpin the linear no-threshold (LNT) model's use for cancer risk assessment. There is a clear distinction here: this effort is about the history of how LNT came to be the regulatory paradigm and model for cancer risk assessment that it is today and not a discussion of the pros and cons of the LNT model. The overarching goal of this effort is to reframe the conversation around low-dose response models in light of this history and to determine how this history influences the scientific understanding of low-dose radiation responses. The timing of this series is intentional, as the International Commission on Radiological Protection (ICRP) has embarked on a mission to review the entire system of radiation protection. This effort necessarily requires rigorous scientific debate that must be based in fact. The history of the LNT model is paramount to this discussion, and it warrants consideration. Unfortunately, rather than engendering respectful debate, the topic of cancer risks associated with low dose radiation exposures has forged two disparate and sometimes contentious camps: (1) low doses, no matter how low, present some form of health risk and (2) an alternative model better represents the actual risks. The video series, conceived by John Cardarelli II, current President of the Health Physics Society (HPS), features Edward Calabrese, professor of toxicology in the School of Public Health and Health Sciences at the University of Massachusetts at Amherst, being interviewed by HPS Past-President Barbara Hamrick, CHP, JD, with support from Daniel Sowers, the Chair of the HPS Public Information Committee, and HPS Executive Director Brett Burk. Emily Caffrey, the Chief Editor of our Ask-the-Experts website (https://hps.org/publicinformation/ate/ ), was invited to watch the completed series as an independent peer reviewer. Further, an email address, factcheck@hps.org, was created to allow for peer-review by the scientific community to facilitate ongoing discussion and allow for corrections to the record as necessary. It is the sincere hope of this team that this work inspires new discussions about the system of radiological protection. We encourage everyone in this field to watch all 22 episodes to be informed about the underpinnings of current regulatory policy in the US.